Performance of warm-season turfgrasses under different water regimes in the Mediterranean climate conditions of Southern Italy - Marchione, Vito; Fracchiolla, Mariano (Italian Journal of Agronomy, 2016)
In Mediterranean areas, very scarce rainfalls during the summer season are a limiting factor to the sowing and managing of turfgrasses. This work evaluates the response to different irrigation regimes (50 or 75% of reference evapotranspiration) of Cynodon dactylon (L.) Pers. cv Transcontinental, Paspalum vaginatum Swartz cv Salam, Pennisetum clandestinum (Chiov.) Hochst. cv AZ1, Stenotaphrum secundatum (Walt.) Kuntze cv Palmetto and Zoysia japonica Steud. cv El Toro. Performance of turfgrasses was evaluated in term of turf quality, colour index and ground cover. Only when rainfalls were scarce, water regime restoring the 75% of the evapotranspiration (ETo) showed significant effects. Under rainy conditions, the restoration of only the 50% of ETo was able to give highly acceptable values. The best performance was observed for Z. japonica, C. dactylon and P. vaginatum, whereas P. clandestinum and S. secundatum showed lower adaptability to water stress.